Therapeutic Effects of Natural Compounds and Small Molecule Inhibitors Targeting Endoplasmic Reticulum Stress in Alzheimer’s Disease - Gao, Xun; Xu, Yuanyuan (Frontiers in Cell and Developmental Biology, 2021)
Alzheimer’s disease (AD) is the most common neurodegenerative disease, characterized by progressive cognitive impairment and memory loss. So far, the pathogenesis of AD has not been fully understood. Research have shown that endoplasmic reticulum (ER) stress and unfolded protein response (UPR) participate in the occurrence and development of AD. Furthermore, various studies, both in vivo and in vitro, have shown that targeting ER stress and ER stress-mediated apoptosis contribute to the recovery of AD. Thus, targeting ER stress and ER stress-mediated apoptosis may be effective for treating AD. In this review, the molecular mechanism of ER stress and ER stress-mediated apoptosis, as well as the theraputic effects of some natural compounds and small molecule inhibitors targeting ER stress and ER stress-mediated apoptosis in AD will be introduced.